Comparative study and outcome of open versus laparoscopic appendectomy: case series of 60 patients - Sharma, Neeraj; Mishra, Mayank; Tripathi, Alok; Rai, Vivekanand (International Surgery Journal, 2017)
Background: Laparoscopic appendectomy combines the advantages of diagnosis and treatment in one procedure with least morbidity. Patients are likely to have less postoperative pain and to be discharged from hospital and return to activities of daily living sooner than those who have undergone open appendectomy. Methods: This prospective study was carried out in the Department of Surgery, Heritage IMS, Varanasi, from May 2016 to May 2017. All the patients were randomly divided into two groups, Group I (Lap App) and Group II (Open App). All quantitative data was compared by independent sample test. All qualitative data was compared by chi-square test. A p-value <0.05 was considered statistically significant. Results: In present study 19 (63%) patients of open appendectomy and 19 (63%) patients of laparoscopic appendectomy were males. 11 (36%) patients of open appendectomy and 11 (36%) laparoscopic appendectomy were females. Conclusions: This study from May 2016 to April 2017 was done on 60 (30 lap and 30 open) patients with clinical diagnosis of acute appendicitis admitted in surgical wards of Heritage Institute of Medical Sciences. In spite of drawback of the increase in duration of surgery, we conclude that laparoscopic appendectomy is better than the open method for acute appendicitis, with less post-operative pain and reduced duration of analgesics used, with lesser incidences of post-operative complications, shorter duration of hospital stays, early return to normal work.